1914 N.J. Laws 65 - (:unkn) unknown (My University, 1914)
Ch. 43, 1: No license to hunt, pursue or kill with a gun or any fire-arm any of the game birds wild animals or fowl of this State, shall be issued to any person under the age of fourteen years, and if any applicant for license shall misrepresent his age he shall be liable to a penalty of twenty dollars, to be sued for and recovered as other penalties under the fish and game laws.
Keywords: HUNTING REGULATION